2017
DOI: 10.1158/1538-7445.am2017-ct047
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT047: Phase 1 dose-escalation study of the CDK inhibitor dinaciclib in combination with the PARP inhibitor veliparib in patients with advanced solid tumors

Abstract: Background: Although PARP inhibition is effective against HR repair-deficient cancers, efficacy is limited by HR proficiency, whether present de novo or as a result of acquired resistance, prompting HR disrupting strategies to sensitize tumor cells. Inhibition of CDK1 and CDK12 compromise HR by blocking BRCA1 phosphorylation, affecting recruitment to sites of DNA damage, and by reducing HR gene expression, respectively. Dinaciclib is a pan-CDK inhibitor that inhibits both CDK1 and CDK12 at nanomolar potency. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This found that twenty-four patients (38 %) had stable disease as the best response with nine progression-free (ClinicalTrials.gov identifier: NCT01434316). [147] These findings show the potential of using this combination strategy to re-establish PARPi sensitivity. Bearing in mind many anti-cancer transition metal complexes achieve potent effects on cell-cycle progression without generating cytotoxic or genotoxic DNA damage, this may be a lucrative area for future investigation.…”
Section: Combination Of Parpi and Cell-cycle Inhibitorsmentioning
confidence: 77%
See 1 more Smart Citation
“…This found that twenty-four patients (38 %) had stable disease as the best response with nine progression-free (ClinicalTrials.gov identifier: NCT01434316). [147] These findings show the potential of using this combination strategy to re-establish PARPi sensitivity. Bearing in mind many anti-cancer transition metal complexes achieve potent effects on cell-cycle progression without generating cytotoxic or genotoxic DNA damage, this may be a lucrative area for future investigation.…”
Section: Combination Of Parpi and Cell-cycle Inhibitorsmentioning
confidence: 77%
“…The combination of veliparib and dinaciclib against patients with advanced solid tumours who are not germline BRCA carriers was evaluated in a phase I study. This found that twenty‐four patients (38 %) had stable disease as the best response with nine progression‐free (ClinicalTrials.gov identifier: NCT01434316) [147] . These findings show the potential of using this combination strategy to re‐establish PARPi sensitivity.…”
Section: Parp Combination Therapy: a Promising Strategymentioning
confidence: 85%
“…At present, several ongoing trials are evaluating the combination of CDK inhibitors with PARP inhibitors (46). The combination of dinaciclib (a CDK 1, 2, 5, 9, and 12 inhibitor) with the PARP inhibitor veliparib has shown preliminary clinical benefit in patients with breast cancer, prostate cancer, ovarian cancer, and other gynecologic malignancies (47). By blocking CDK12, CDK1, or CDK2, BRCA wild-type cancer cells turn into HR-deficient cells through inhibition of BRCA1 expression and phosphorylation (48, 49) and, thus, become more susceptible to synthetic lethality induced by PARP inhibitors (4649).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, there is significant heterogeneity in the response of individual tumors to CDK4/6 inhibitors [48, 49] and it has therefore become imperative that we better understand biomarkers that predict sensitivity to these agents. Equally important is the problem of resistance to CDK4/6 inhibitors – for example, in breast cancer nearly all tumors acquire resistance to these agents after prolonged therapy, and the mechanisms underlying this are also poorly understood [50].…”
Section: Improving the Efficacy Of Cdk4/6 Inhibitors As Cancer Therapymentioning
confidence: 99%